Digital Safety During Online Learning: What We Do to Protect Our Student? - Dewanto Muhammad Zulqadri; Ali Mustadi; Heri Retnawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The article aims to uncover security risks that may occur during online learning, as well as preventive measures that can be taken to avoid these threats. This study uses a combination of two methods, namely, web mining and literature review. From the results of web mining, it is found that the website articles have not provided much explanation about efforts to protect against threats on the internet, from the results of the literature review the researchers revealed that several threats that can occur on the internet, namely phishing, scamming, fraud, cyberbullying, viruses, privacy and personal data issues, and obscene or pornographic content. This study also provides three important steps in protecting children from internet threats during online learning, including assistance in accessing internet content, education about internet safety and personal data protection, as well as an introduction to Digital Citizenship and ethics in cyberspace. Keywords: Digital Safety, Online Learning Safety, Digital Citizenship